Neuropeptide Y and chronic kidney disease progression: a cohort study. Issue 10 (23rd January 2018) - Zoccali, Carmine; D'Arrigo, Graziella; Leonardis, Daniela; Pizzini, Patrizia; Postorino, Maurizio; Tripepi, Giovanni; Mallamaci, Francesca; van den Brand, Jan; van Zuilen, Arjan; Wetzels, Jack; Bots, Michiel L; Blankestijn, Peter
ABSTRACT: Background: Neuropeptide Y (NPY) is a sympathetic neurotransmitter that has been implicated in various disorders including obesity, gastrointestinal and cardiovascular diseases. Methods: We investigated the relationship between circulating NPY and the progression of the glomerular filtration rate (GFR) and proteinuria and the risk for a combined renal endpoint (>30% GFR loss, dialysis/transplantation) in two European chronic kidney disease (CKD) cohorts including follow-up of 753 and 576 patients for 36 and 57 months, respectively. Results: Average plasma NPY was 104 ± 32 pmol/L in the first CKD cohort and 119 ± 41 pmol/L in the second one. In separate analyses of the two cohorts, NPY associated with the progression of the estimated GFR (eGFR) and proteinuria over time in both unadjusted and adjusted {eGFR: −3.60 mL/min/1.73 m 2 [95% confidence interval (CI): −4.46 to − 2.74] P < 0.001 and −0.83 mL/min/1.73 m 2 (−1.41 to − 0.25, P = 0.005); proteinuria: 0.18 g/24 h (0.11–0.25) P < 0.001 and 0.07 g/24 h (0.005–0.14) P = 0.033} analyses by the mixed linear model. Accordingly, in a combined analysis of the two cohorts accounting for the competitive risk of death (Fine and Gray model), NPY predicted (P = 0.005) the renal endpoint [sub-distribution hazard ratio (SHR): 1.09; 95% CI: 1.03–1.16; P = 0.005] and the SHR in the first cohort (1.14, 95% CI: 1.04–1.25) did not differ (P = 0.25) from that in the second cohort (1.06, 95% CI: 0.98–1.15). Conclusions: NPY associates with proteinuria and faster CKD progression as well as with a higher risk of kidney failure. These findings suggest that the sympathetic system and/or properties intrinsic to the NPY molecule may play a role in CKD progression.